Genome-wide Scan of African-American and White Families for Linkage to Myopia - CINER, ELISE (2008)
PURPOSE: To identify myopia susceptibility genes influencing common myopia in 94 African-American and 36 White families. DESIGN: A prospective study of families with myopia consisting of a minimum of two individuals affected with myopia. METHODS: Extended families consisting of at least two siblings affected with myopia were ascertained. A genome-wide linkage scan using 387 markers was conducted by the Center for Inherited Disease Research. Linkage analyses were conducted with parametric and nonparametric methods. Model-free linkage analysis was performed maximizing over penetrance and over dominance (that is, fitting a wide range of both dominant and recessive models). RESULTS: Under the model-free analysis, the maximum two point heterogeneity logarithm of the odds score (MALOD) was 2.87 at D6S1009 in the White cohort and the maximum multipoint MALOD was 2.42 at D12S373-D12S1042 in the same cohort. The nonpara-metric linkage (NPL) maximum multipoint at D6S1035 had a P value of .005. An overall multipoint NPL score was obtained by combining NPL scores from both populations. The highest combined NPL score was observed at D20S478 with a significant P value of .008. Suggestive evidence of linkage in the White cohort mapped to a previously mapped locus on chromosome 11 at D11S1981 (NPL = 2.14; P = .02). CONCLUSIONS: Suggestive evidence of linkage to myopia in both African Americans and Whites was seen on chromosome 20 and became more significant when the scores were combined for both groups. The locus on chromosome 11 independently confirms a report by Hammond and associates mapping a myopia quantitative trait locus to this region.